Local Government Financial Performance and Its Affecting Factors - Saqina, Tiya Maylafaz; Husriah; Fatmala, Wilda (International Journal of Multidisciplinary Learners, 2025)
The purpose of this study was to determine the Financial Performance of the South Buton Regency Regional Government and the Factors that Influence It. This research was conducted at the Regional Finance and Asset Agency of South Buton Regency. The population in this study was the Regional Revenue and Expenditure Budget Realization Report (APBD). The sample used in this study was the Regional Revenue and Expenditure Budget Realization Report of South Buton Regency for 2016-2022. The type of research used in this study is a descriptive approach with a quantitative method using primary data and secondary data. The data collection techniques used in this study are documentation and interview techniques. The data technique uses ratio analysis and SPSS 29. The results of the study indicate that the percentage of Regional Financial Independence is in an instructive pattern with very low financial capability, while the Regional Government Financial Performance based on the Effectiveness Ratio is in the Effective criteria range, based on the Activity Ratio indicating that the South Buton Regency Regional Government prioritizes Operating Expenditures and Capital Expenditures, while the Growth Ratio shows that the Regional Original Income fluctuates from year to year. Balancing funds do not have an impact on the financial performance of the South Buton Regency Regional Government, Regional Expenditure does not have an impact on financial performance, Regional Taxes do not have an impact on financial performance.